Effects of dietary zinc oxide nanoparticles supplementation on broiler growth performance, zinc retention, liver health status, and gastrointestinal microbial load - Mohd Yusof, Hidayat; Abdul Rahman, Nor'Aini; Mohamad, Rosfarizan; Zaidan, Uswatun Hasanah; Arshad, Muhammad Aiman; Samsudin, Anjas Asmara (Elsevier BV, 2023)
Background: Zinc (Zn) is an essential trace element for poultry health and biological functions. Inorganic Zn, like Zn oxide and Zn sulfate, was commonly used in poultry feed due to its low cost. However, the bioavailability of inorganic Zn is low, leading to a high level of Zn being added to the feed and resulting in other issues. Zinc oxide nanoparticles (ZnO NPs) have emerged as a promising alternative to their bulkier counterparts, but concerns about their safety persist. Therefore, this study aimed to evaluate the potential benefits and toxicity of dietary ZnO NPs as a feed supplement and antibacterial agent in broiler chickens. Methods: 180 broiler chicks (Cobb500) were randomly allocated to five dietary treatment groups (36 birds/group). The experimental treatment groups were as follows: (G1) basal diet supplemented with 100 mg kgˆ’1 ZnO (control group), (G2-G5) basal diet supplemented with 10, 40, 70, and 100 mg kgˆ’1 ZnO NPs. The effects of dietary ZnO NPs at different inclusion levels were studied by measuring growth performance (FI, BWG, and FCR), Zn retention, liver enzyme activity, lymphoid organ weight, and gastrointestinal microbial load. Results: The results showed that dietary ZnO and different levels of ZnO NPs inclusion had no effect on broiler growth performance (p > 0.05). The birds fed dietary ZnO NPs retained significantly more Zn than the control group (p < 0.05), lowering feces Zn excretion. The supplementation of ZnO NPs did not reduce lymphoid organs weight; in fact, a notable increase in weight was observed in groups supplemented with higher levels of ZnO NPs when compared to the control group. Furthermore, no significant increase in liver weight (p > 0.05) or enzymatic activities (AST and ALT) were observed in birds fed ZnO NPs, indicating no liver damage occurred. ZnO NPs at 100 mg kgˆ’1 in the diet showed antibacterial effects, reducing Enterococcus spp. and E. coli count significantly, without affecting commensal bacteria (lactic acid bacteria) count. Conclusion: The inclusion of ZnO NPs to broiler chicken feed as a Zn source had no negative effects on growth or health. Additionally, it increased Zn absorption and bioavailability, reduced Zn excretion, and exhibited potential antibacterial activity against tested pathogens.